Design maintenance for lighthouse / Muhamad Rashid Ab Aziz - Ab Aziz, Muhamad Rashid (Faculty of Architecture, Planning and Surveying, 2009)
As lighthouses have become less essential to navigation, many of their historic structures have faced demolition or neglect. So, this final project will enlighten with more detail regarding the maintenance works for lighthouse. This research of the study will involves marine department of Malaysia as a government organization that responsible to manage lighthouses. The aim of this final project is to investigate the implementation of marine department to maintain the lighthouse and suggest the best design maintenance for lighthouse. To support this research, four lighthouses have been taken as case studies. The data gathered from observation, condition survey and interview conducted at the site. It is hoped that the overall findings of the study will be beneficial for further research that can be developed in this particular area. Besides that, the analysis is made to achieve the objective of this study. Conclusion and recommendation also made in the last chapter to achieve the objective of the study. From this study, the author hopes that it would give clear awareness to us why the important of lighthouse to be maintain.